Enantioselective liver microsomal sulphoxidation of albendazole in cattle: effect of nutritional status - Virkel, Guillermo Leon (2000)
1. The enantioselective liver microsomal sulphoxidation of the benzimidazole anthelmintic, albendazole (ABZ), by cattle liver microsomes has been investigated. The influence of nutritional condition on this biotransformation process was also characterized. 2. ABZ was oxidized to its sulphoxide metabolite (ABZSO) in a NADPH concentration-dependent reaction and the (+) and (-) ABZSO enantiomers formed were identified. 3. Vmax (0.27 nmol ABZSO formed per min x mg(-1) microsomal protein) and Km (15.10 microM) for ABZ sulphoxidation by cattle liver microsomes were obtained. Different Vmax (0.11 and 0.16 nmol x min(-1) x mg(-1)) and Km (9.40 and 26.70 microM) characterized the enantioselective formation of (+) and (-) ABZSO antipodes, respectively. 4. Free fatty acid (FFA) concentrations and beta-hydroxybutyrate concentrations (beta-OHB) in serum and liver homogenates were significantly higher in feed-restricted (poor nutritional condition) compared with control animals in an optimal nutritional status. Serum protein concentrations and liver cytosolic glucose 6-phosphate dehydrogenase (G6PD) activity were significantly lower in the feed-restricted compared with control calf. 5. Animal nutritional condition affected the pattern of ABZ sulphoxidation. A higher Km for (total) ABZSO and (+) ABZSO production was observed in the calf subjected to a period of undernutrition. 6. A nutritionally induced impairment in the affinity of microsomal mixed-function oxidases responsible of ABZ oxidation may be responsible for the observed changes in the liver microsomal sulphoxidation of ABZ in the feed-restricted calf. Furthermore, undernutrition may affect primarily the FMO-mediated formation of (+) ABZSO. These in vitro observations agree with the changes observed in vivo following the administration of ABZ to the calf subjected to a dietary restriction.